2019
DOI: 10.1124/jpet.119.257931
|View full text |Cite
|
Sign up to set email alerts
|

Short Periods of Hypoxia Upregulate Sphingosine Kinase 1 and Increase Vasodilation of Arteries to Sphingosine 1-Phosphate (S1P) via S1P3

Abstract: Sphingosine kinase [(SK), isoforms SK1 and SK2] catalyzes the formation of the bioactive lipid, sphingosine 1-phosphate (S1P). This can be exported from cells and bind to S1P receptors to modulate vascular function. We investigated the effect of shortterm hypoxia on SK1 expression and the response of arteries to S1P. SK1 expression in rat aortic and coronary artery endothelial cells was studied using immunofluorescence and confocal microscopy. Responses of rat aortic rings were studied using wire myography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…A molecular study of arterial responses under short-term hypoxic conditions demonstrated arterial dilatation mediated by various receptors. [28] In the present study, although patients were examined during the acute phase of disease, the observed changes in PD may have been caused by short-term hypoxia. Similarly, studies that investigated the relationship between retinal veins and oxygen saturation reported a wider diameter of retinal veins under lower arterial oxygen saturation levels.…”
Section: Discussionmentioning
confidence: 80%
“…A molecular study of arterial responses under short-term hypoxic conditions demonstrated arterial dilatation mediated by various receptors. [28] In the present study, although patients were examined during the acute phase of disease, the observed changes in PD may have been caused by short-term hypoxia. Similarly, studies that investigated the relationship between retinal veins and oxygen saturation reported a wider diameter of retinal veins under lower arterial oxygen saturation levels.…”
Section: Discussionmentioning
confidence: 80%
“…Endothelial cells are known to be exquisitely sensitive to oxygen depletion even after short intervals of time. [46][47][48][49] Integrin cell adhesion molecules displayed on the cell surface regulate the interaction between endothelial cells, the extracellular matrix, and circulating intraluminal cell populations. 17,50 Here we showed ITGA5 protein localized to the surface of kEPCs was modulated first by the binding of mature miR-218-5p to ITGA5 mRNA transcript within the coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The investigations reported here outline the specific function of one mature miRNA, miR-218-5p, in mammalian kEPCs responding to a hypoxic environment (Figure 8). Endothelial cells are known to be exquisitely sensitive to oxygen depletion even after short intervals of time 46 49 . Integrin cell adhesion molecules displayed on the cell surface regulate the interaction between endothelial cells, the extracellular matrix, and circulating intraluminal cell populations 17 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…S1P2 also induces senescence-associated damage in young ECs ( 277 ). Under hypoxic conditions, S1P3 is activated in ECs, resulting in NO-dependent vasodilation ( 278 ).…”
Section: Adipose Tissue-derived Bioactive Materialsmentioning
confidence: 99%